Voltammetric Method for Determining Ferric Ions with Quercetin - Olgac, Nursel; Karakus, Erman; Sahin, Yucel; Liv, Lokman (WILEY-V C H VERLAG GMBH, 2021)
A novel, simple, rapid, inexpensive, highly sensitive voltammetric method developed for determining ferric ions with quercetin in water samples and iron supplements using a disposable bare pencil graphite electrode is described. The limit of detection and analytical ranges for the ferric ions were 3.6 nM and 17.9-716.0 nM, respectively. The results with the water samples were compared with those obtained from a potentiometric auto-titration system, and the method's accuracy was tested using certified reference material. The complex stoichiometry and electrode reaction were also systematically investigated with UV-visible spectrophotometry, H-1-NMR spectroscopy and voltammetry.
Keywords: Ferric ions; quercetin; pencil graphite electrode; water samples; iron supplements; REDUCED GRAPHENE OXIDE; IRON III; SELECTIVE DETERMINATION; SOLVENT-EXTRACTION; TAP WATER; IRON(III); ELECTRODE; COMPLEX; ANTIOXIDANT; Chemistry; Electrochemistry